Upaya Guru Madrasah Tsanawiyah DDI Padanglolo Tingkatkan Minat Siswa Kelas VIII pada Mata Pelajaran Fiqih - Hanawiah hanawiah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Studying and understanding Fiqh subjects for students is very important, because this knowledge will be applied directly in daily life, so it is necessary to cultivate interest in learning in these subjects. With interest, students will be more interested and enthusiastic during the learning process, the greater the interest of students, the easier it will be to understand the lesson. This study’s purpose is knowing the teacher's efforts and to find out the obstacles faced by teachers in order to increase the learning interest of class VIII students in Fiqh subjects at Madrasah Tsanawiyah DDI Padanglolo. The research method used is a qualitative method, namely data collection in a natural setting with the intention of interpreting the phenomena that occur where the researcher is the key instrument, sampling of data sources is carried out purposively and snowball, collection techniques are triangulation, data analysis is qualitative, where the research results qualitative emphasizes more on meaning than generalization. The analysis of qualitative research data from the Miles and Huberman model was carried out through the steps of 1) Data reduction, 2) Datadisplay, 3) Drawing conclusions or verification. The results of this study are to increase the interest of class VIII students in the subject of Fiqh at Madrasah Tsanawiyah DDI Padanglolo through the provision of motivation, the use of various learning methods (lectures, discussions, practices, etc.), as well as providing advice. The obstacles faced are the character of students, lack of student awareness and lack of learning support tools.